2015
DOI: 10.1007/s00419-015-1098-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-circular nano-inclusions with interface effects that achieve uniform internal strain fields in an elastic plane under anti-plane shear

Abstract: This paper verifies the existence of a single non-circular nano-inclusion with interface effect that achieves a uniform internal strain field in an elastic plane under uniform remote anti-plane shear loadings. The uniform strain field inside such a non-circular inclusion is prescribed via perturbations of the uniform strain field inside the analogous circular inclusion, and the unknown (non-circular) inclusion shape is characterized by a conformal mapping whose unknown coefficients are determined by a system o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 27 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Recently, Dai and Gao and Dai et al showed that certain non-circular inhomogeneities (with conventional interface effects only, no gradient effects) could also achieve uniform internal stress field under uniform remote anti-plane shear loadings [26,27]. It is interesting to probe whether non-circular inhomogeneities with uniform internal stress fields still exist when interface gradient effects are taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dai and Gao and Dai et al showed that certain non-circular inhomogeneities (with conventional interface effects only, no gradient effects) could also achieve uniform internal stress field under uniform remote anti-plane shear loadings [26,27]. It is interesting to probe whether non-circular inhomogeneities with uniform internal stress fields still exist when interface gradient effects are taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…to calculate the Jacobian matrix in the corresponding Newton-Raphson iteration. For detailed implementation of the Newton-Raphson iteration, one can refer to [13,14]. Once the finite coefficients a j (j = 1.N) are determined, it is easy to obtain the actual shape of the periodic harmonic holes in physical plane from the corresponding (truncated) mapping (8).…”
Section: C(r(s))mentioning
confidence: 99%
“…In particular, we use σ = e i θ ( 0 θ 2 π ) to denote the unit circle (where | ξ | = 1 ) in the ξ -plane that corresponds to the curve L in the z -plane. Using the mapping of equation (5), we can describe the term e i α on the right-hand side of equation (4) by [14]…”
Section: Solution Proceduresmentioning
confidence: 99%
“…In such cases, the contribution of surface or interface effects [12, 13] (usually manifested as surface or interface tension or surface or interface elasticity) around internal nanosized holes or inclusions are known to play an important role in the determination of the corresponding stress distributions. The resulting inverse problems for the identification of optimal shapes in nanostructures or nanocomposites then become extremely challenging, perhaps explaining why so few investigations can be found in this area (see, for example, Dai and Gao [14]). In this paper, we make progress in this direction by incorporating the contribution of surface or interface effects and subsequently developing an efficient method for the construction of harmonic nanosize holes in an elastic plane subjected to uniform remote loading.…”
Section: Introductionmentioning
confidence: 99%